2002
DOI: 10.1007/pl00012663
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care, defensive behavior, and sociality in neotropical Goniosoma harvestmen (Arachnida, Opiliones)

Abstract: Goniosoma includes large and conspicuous species of harvestmen that occur exclusively in the Brazilian Atlantic forest. This paper reports on the parental activities, defensive behavior, and gregariousness of five species of Goniosoma, and also summarizes the published biological data for the genus. The behavioral patterns within the genus are discussed and a hypothesis for the emergence of gregariousness in the group is presented. Several Goniosoma live inside caves, mainly as trogloxenes. Although species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 35 publications
3
27
2
5
Order By: Relevance
“…Many gonyleptids show gregarious habits, and among the representatives of the subfamily Goniosomatinae, this behavior is especially common (Machado, 2002). Recently, it was demonstrated that the defensive secretion of Goniosoma aff.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many gonyleptids show gregarious habits, and among the representatives of the subfamily Goniosomatinae, this behavior is especially common (Machado, 2002). Recently, it was demonstrated that the defensive secretion of Goniosoma aff.…”
Section: Discussionmentioning
confidence: 99%
“…All individuals of G. longipes used in this study were collected inside caves at the Parque Florestal do Itapetinga (23-15 ¶S, 46-45 ¶W, 900-to 1300-m altitude, 1600 mm rain/year), Atibaia, São Paulo state, southeastern Brazil (for details on the study site, see Machado andOliveira, 1998 andMachado et al, 2000). In the laboratory, adult G. longipes were maintained in a communal terrarium (60 Â 40 cm base, 35 cm high) containing cotton wetted with water to maintain the humidity and fed with dead insects twice a week.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations